2019
DOI: 10.29221/jce.2019.22.4.105
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Profile Analysis of Primary Students' Homework Behavior : Homework time and effort

Abstract: s' homework feedback, homework purpose and achievement goal orientations were statistic ally associated with the homework learning types. The students with the more adaptive h omework learning types tended to have a mastery-goal orientation and learning-oriented homework purpose. Also they reported to have more homework feedback from their teach ers. These findings shed some light on the generally inconsistent pattern of results on ho mework research and also emphasize the value of the person-centered approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…Because this is the first investigation that applied the LPA to a broad spectrum of homework characteristics, we have no specific hypothesis concerning the number of homework characteristics profiles that would exist. On the other hand, in line with our general expectation as informed by prior studies (Flunger et al, 2015 , 2017 ; Shin & Sohn, 2019 ; Valle et al, 2019 ), we identified profiles containing high homework time (i.e., High Time and Frequency/Moderate With Others ), low homework time (i.e., Low ), and moderate homework time (i.e., Moderate Time/High With Others, Low Frequency/Moderate With Others, Moderate Time/High Frequency/Low With Others ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Because this is the first investigation that applied the LPA to a broad spectrum of homework characteristics, we have no specific hypothesis concerning the number of homework characteristics profiles that would exist. On the other hand, in line with our general expectation as informed by prior studies (Flunger et al, 2015 , 2017 ; Shin & Sohn, 2019 ; Valle et al, 2019 ), we identified profiles containing high homework time (i.e., High Time and Frequency/Moderate With Others ), low homework time (i.e., Low ), and moderate homework time (i.e., Moderate Time/High With Others, Low Frequency/Moderate With Others, Moderate Time/High Frequency/Low With Others ).…”
Section: Discussionsupporting
confidence: 90%
“…Since our study is the first to apply a person-centered approach to a broad range of homework characteristics, we have no specific hypothesis concerning the number of homework characteristic profiles that would emerge. On the other hand, congruent with previous studies adopting a person-centered approach drawing from homework time and homework effort/homework time management (Flunger et al, 2015 , 2017 ; Shin & Sohn, 2019 ; Valle et al, 2019 ), several profiles may emerge, including a profile containing high homework time, a profile containing low homework time, and profiles with varying degrees of homework time and other homework characteristics.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Some studies [ 22 24 ] have been conducted based on the assumption that there are various subgroups according to the emotion regulation strategy, and the more positive emotion regulation strategies were used, the lower Psychiatric Symptoms was. However, there are limitations to this approach.…”
Section: Introductionmentioning
confidence: 99%